《左傳》“請安”及相關紀事釋義辨疑———《左傳》與《儀禮》互證之一例: An Interpretation of the Word “Qingan” and Related Matters as Recorded in Zuozhuan: An Evidence of Agreements between Zuozhuan and Yili - 許子濱 (人文中國學報, 2015)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 據《左傳》所載，魯昭公奔齊後，多次朝見齊景公。昭公二十七年這一次，景公請求設饗禮招待昭公。子家羈料知景公只是借饗爲名，實邀昭公飲酒，於是對昭公説：“時常朝見於其人之朝，又行甚麽饗呢？大概是飲酒吧。”結果正如子家羈所料。當日行宴之所，大概就在景公的寢宫之中。“使宰獻”謂使宰獻爵。蓋用士一獻之禮。“請安”指景公命人（蓋爲司正）請昭公安留。“重”只能是景公自稱其妻之名，“請使重見”也只能是景公自請。依禮，君命“請安”，賓答應後，便可進行旅酬以下的儀節。只有昭公答應安留，才能“請使重見”。《傳》文所述的“使宰獻，而請安”，與《儀禮•燕禮》等篇所記飲酒儀節契合無間。“請使重見”，應在旅酬後宴飲之時。景公不親自向昭公敬酒，而是使宰獻酬，又命人留賓，就像君飲大夫酒那樣。這樣做，顯然不以兩君之禮對待昭公，竟將他比作大夫，輕慢之心昭然若揭。景公請求讓夫人與昭公相見，只爲了使她參與宴飲，更顯得褻慢輕佻。在子家羈看來，讓夫人接待外賓，男女雜坐，相與宴飲，失禮已甚。就在夫人出現之前，子家羈與昭公遽然離開，避見夫人。 As recorded in Zuozhuan, after driven into exile by Ji Pingzi (季平子), Lord Zhao of Lu (魯昭公) sought refuge in Qi (齊) and resided in Yun (鄆) on the Qi border thereafter. One day, Lord Jing of Qi (齊景公)invited Lord Zhao to a banquet. Zijia Ji (子家羈, one of Lord Zhao’s high officers) who accompanied Lord Zhao said that Lord Jing in fact did not intend to host a formal feast in honour of Lord Zhao but rather invite him to drink wine merely for amusement. It turned out that Duke Jing did not treat Lord Zhao according to proper etiquette, just as what Zijia Ji had anticipated. Instead of offering wine to Lord Zhao by himself, Lord Jing sent Zai (宰, Duke Jing’s family retainer) serving as the master of ceremonies to toast the guest. Zai thereupon asked the guest to sit down and carry on drinking. Duke Jing asked for Lord Zhao’s permission to let his concubine Chong (重) to join them. Zijia Ji and Lord Zhao left the venue before Chong appeared. There is one keyword namely “Qingan” (請安) used in the narrative that has attracted much discussions since ancient times. The present article proposes an approach by combining meaning with syntax and taking both the narrative and ritual into consideration. It argues that the word refers to a specific etiquette of banquet, and that the word conforms with its counterpart in Yili (儀禮). This is evident of the agreement between Zuozhuan and Yili. Lord Jing’s rhetoric barely masks the reality of treating Lord Zhao as an implicit officer instead of a ruler. Inviting Chong to join the banquet also violated ritual propriety.